Diagnostics of psychoemotional readiness for competitive activities of young basketball players - Kremneva V.N.; Solodovnik E.M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the level of personal anxiety, self-esteem and the state of mental reliability of young basketball players. Methods and structure of the study. The basis for the study was the Olympic reserve sports school «Kupchinsky Olympus» in the Frunzensky district of St. Petersburg (hereinafter referred to as «Olympus»). 10 girls born in 2009 of the training stage group (sports specialization stage) «Olympus» took part in the survey. To conduct the study, two Spielberger questionnaires were used. Results and conclusions. The results of the first survey (Study of situational anxiety) showed that a high level of anxiety was detected in 40% of respondents, 40% had an average level of anxiety, and 20% had a low level of anxiety. The results of the second questionnaire (Self-Assessment of Anxiety) did not reveal a low level of anxiety among players in general, 60% of girls were identified with an average level, and 40% with a high level of anxiety. The average level of mental reliability for the four components was determined as follows: a reduced level of reliability compared to the average data for 20% of respondents, an average level for 40%, and an increased level of reliability for 40% compared to the optimal data.